Nghiên cứu chế tạo màng mỏng Cu2O bằng phương pháp lắng đọng hóa học pha hơi - Huỳnh, Lê Văn (Vietnam Journal of Chemistry, 2017)
Cu2O thin films are widely used in many fields such as: solar panel, catalysts for chemical reactions, especially in the field of electronics. Cu2O thin films manufacture by vapor phase deposition methods chemical. This is the method by which solid material, is deposited from the vapor phase, through the the chemical reaction, near the surface to be heated. Obtained in the form of solids coatings, powder or the the crystal form. The advantage of CVD method is able to make the thin film with evenly thickness and less porous, even when complicated shapes. In this paper is the research results on Cu2O thin films by method CVD from Cu(Acac)2. XRD and SEM research showed that Cu2O crystals with cubic structure, temperature affects the surface states of thin films. Keywords. Cu2O thin film fabrication, chemical vapor deposition.